KARAKTERISASI DAN STUDI SINERGI ANALOG KURKUMIN DARI SENYAWA 4-METOKSIBENZALDEHIDA SEBAGAI ANTIDIABETES DENGAN METODE IODIN (CHARACTERIZATION AND SYNERGY STUDY OF CURCUMIN ANALOGS FROM 4-METHOXYBENZALDEHYDE COMPOUND AS AN ANTIDIABETIC USING IODINE METHOD) - Khoirotun Nafillah; Chairil Anwar (Indonesian Journal of Pure and Applied Chemistry, 2023)
Curcumin is the main component of turmeric with various biological activities, one of which is antidiabetic. However, curcumin has low bioavailability and fast metabolism, so repeated doses are required if used as a medicine. Curcumin analogs have better bioavailability than curcumin. This study aims to synthesize curcumin analog from 4-methoxybenzaldehyde and monoketone (cyclohexanone and cyclopentanone), and their synergism effect using iodine method. The compounds A and B have been synthesized using Claisen-Schmidt condensation from benzaldehyde derivatives using KOH 8% and ethanol as solvent. The results showed that the curcumin analogs A and B were yellow solids with yields of 31,13% and 31,87%, respectively. The structure of products was characterized by FTIR, DI-MS, 1H- and 13C-NMR, showed that curcumin analogs A is 2,6-bis(4-methoxybenzylidene)cyclohexanone and curcumin analogs B is 2,6-bis(4-methoxybenzylidene)cyclopentanone. α-amylase inhibition assay of curcumin analogs A and B were performed by formation of amylum-iodine complex with UV-vis spectrophotometer at wavelength of 600 nm, showed that 33,03% and 91,5% at concentration 1 mM. Synergy studies with ferulic acid indicated that compound A 99,23% at a concentration ratio (1:8) and B 99,14% (1:4). This indicates a synergy between curcumin analogs and ferulic acid as an inhibitor of the α-amylase.